Do entrapment, injuries, outcomes and potential for self-extrication vary with age? A pre-specified analysis of the UK trauma registry (TARN) - Tim Nutbeam; Anthony Kehoe; Rob Fenwick; Jason Smith; Omar Bouamra; Lee Wallis; Willem Stassen (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine, 2022)
Abstract Background Motor vehicle collisions (MVCs), particularly those associated with entrapment, are a common cause of major trauma. Current extrication methods are focused on spinal movement minimisation and mitigation, but for many patients self-extrication may be an appropriate alternative. Older drivers and passengers are increasingly injured in MVCs and may be at an increased risk of entrapment and its deleterious effects. The aim of this study is to describe the injuries, trapped status, outcomes, and potential for self-extrication for patients following an MVC across a range of age groups. Methods This is a retrospective study using the Trauma Audit and Research Network (TARN) database. Patients were included if they were admitted to an English hospital following an MVC from 2012 to 2019. Patients were excluded when their outcomes were not known or if they were secondary transfers. Simple descriptive analysis was used across the age groups: 16–59, 60–69, 70–79 and 80+  years. Logistic regression was performed to develop a model with known confounders, considering the odds of death by age group, and examining any interaction between age and trapped status with mortality. Results 70,027 patients met the inclusion criteria. Older patients were more likely to be trapped and to die following an MVC (p < 0.0001). Head, abdominal and limb injuries were more common in the young with thoracic and spinal injuries being more common in older patients (all p < 0.0001). No statistical difference was found between the age groups in relation to ability to self-extricate. After adjustment for confounders, the 80 + age group were more likely to die if they were trapped; adjusted OR trapped 30.2 (19.8–46), not trapped 24.2 (20.1–29.2). Conclusions Patients over the age of 80 are more likely to die when trapped following an MVC. Self-extrication should be considered the primary route of egress for patients of all ages unless it is clearly impracticable or unachievable. For those patients who cannot self-extricate, a minimally invasive extrication approach should be employed to minimise entrapment time.